A Political Romance - Sterne, Laurence (Saga Egmont, 2022)
Considered scandalous at the time, \'A Political Romance\' is a satirical look at the relationship between the Church and the Law. Written before Sterne\'s \'Tristram Shandy\' books (later adapted for film, as \'A Cock and Bull Story, starring Steve Coogan and Rob Brydon), it tells the tale of a small-town quarrel between a dean, an archbishop, and an ecclesiastical lawyer. While you might think their argument might be something to do with spiritual issues, it is actually over a greatcoat. Did this book deserve to be burned after its publication? Decide for yourself, with this superb read from one of the greats of the 18th Century.